2023
DOI: 10.1186/s41182-023-00507-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical characteristics of children with confirmed COVID-19 infection in a tertiary referral hospital in Manila, Philippines

Abstract: Background COVID-19 has challenged the under-resourced health systems of low- and middle-income countries, significantly affecting child health. Available published data on Filipino children with COVID-19 infection are limited. This study aims to describe the epidemiological and clinical characteristics of pediatric patients with confirmed COVID-19 in an infectious disease hospital in Manila, Philippines. Main text This cross-sectional study review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
1
1
Order By: Relevance
“…The most common reasons for hospitalization in the current study included fever, followed by cough. The results obtained corroborated previous epidemiological studies, where fever, cough, rhinorrhea, respiratory distress, sore throat, vomiting, and diarrhea were the most commonly reported symptoms [27][28][29]50]. The other symptoms included headaches, anorexia, myalgia, nausea, and fatigue.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The most common reasons for hospitalization in the current study included fever, followed by cough. The results obtained corroborated previous epidemiological studies, where fever, cough, rhinorrhea, respiratory distress, sore throat, vomiting, and diarrhea were the most commonly reported symptoms [27][28][29]50]. The other symptoms included headaches, anorexia, myalgia, nausea, and fatigue.…”
Section: Discussionsupporting
confidence: 89%
“…Our study exhibited a higher positivity rate than that reported in the initial phases of the pandemic, where the positivity rate was around 2% in children [26,27]. Nevertheless, a marked increase in the number of children contracting COVID-19 infection was witnessed over time, largely attributable to changing COVID-19 associated symptoms, laboratory testing capacity, and the emergence of different variants [28,29].…”
Section: Discussioncontrasting
confidence: 54%
“…The number of admissions of pediatric patients with COVID-19 is increasing since the Omicron strain become endemic ( 10 , 11 ). In Tochigi Prefecture, the number of pediatric patients with COVID-19 increased from the 6th wave (the Omicron epidemic period in Japan), and the number of hospitalized cases admitted to JCMCT increased significantly.…”
Section: Discussionmentioning
confidence: 99%